Student and faculty perceptions of nutrition education in medical school - Hawk, Victoria H; Kapounová, Zlata; Krobot, Martin; Spáčílová, Veronika; Lagová, Eliška; Podborská, Michaela; Haldeman, Lauren (Clinical nutrition ESPEN, 2022)
BACKGROUND & AIM: There is abundant evidence to support the beneficial role of nutrition in the prevention, management and treatment of many health conditions including non-communicable diseases and malnutrition. Despite the increasing prevalence of these conditions around the world, research over the past decades has identified that many medical schools lack adequate nutrition education and training for medical students. With the Czech Republic not represented in these findings, this qualitative study aimed to assess and describe the perceptions of nutrition education at a Czech medical school. METHODS: Thirty-six participants, including students in all grades (n = 30) and faculty members from different disciplines (n = 6), completed individual, semi-structured interviews. Interviews were audio-recorded and transcribed verbatim. Inductive coding and thematic analysis were used to analyze data and identify key themes. RESULTS: Participants emphasized the important and wide-ranging role of nutrition, describing it as significant and essential for both prevention and treatment of many medical conditions. The first main theme, 'Nutrition in Medical Care and Health' identified support for the important role that nutrition plays in medical care and health. Participants acknowledged that doctors have an important role to promote good nutrition and thus require sufficient education in medical school to offer general nutrition information to patients. In the second theme, 'Nutrition Education in the Current Curriculum' some participants acknowledged that while the medical school offers a good theoretical education about nutrition, and training for specific populations such as pediatrics and oncology, overall, the current education about nutrition was 'inadequate,' not emphasized like other subjects and lacked practical application in clinical practice. The third main theme 'Opportunities for Nutrition Education in Medical School' identified the students' interest in learning more about nutrition to improve their knowledge in preparation for future practice and to promote healthy eating during medical school. In addition to identifying specific topics of interest, the participants shared preferred methods of learning nutrition information. CONCLUSIONS: The participants in this study recognized the importance of nutrition in medical care and perceived that nutrition education is not emphasized consistently in medical school. Students desired additional nutrition education to include current topics, promote self-care, and improve the emphasis in clinical training.
Keywords: Qualitative Research; Medical students; dítě; Faculty; školy lékařské; lidé; Students, Medical; Curriculum; studenti lékařství; Qualitative research; Czech Republic; Medical school; akademický sbor; kurikulum; Child; Nutrition education; Schools, Medical; kvalitativní výzkum; Humans